Damage and deformation in composite sandwich panels exposed to multiple and single explosive blasts. (June 2017) - Arora, H.; Del Linz, P.; Dear, J.P.
Highlights: Large-scale blast experiments on sandwich composites using 38.8–100 kg TNT equivalent charges are presented. Parameters relevant to real applications are showcased here such as reduced stand-off and multiple blast exposures. Transient displacement histories are presented for multiple sandwich materials, with their respective trends with increasing blast intensity. To describe how damage initiates and develops during a given blast event. Abstract: The blast resistance of glass-fibre reinforced polymer (GFRP) sandwich structures has been investigated for increasing shock intensity and for multiple blast exposures. In this study, sandwich panels of 1.6 m x 1.3 m were subjected to 30 kg charges of C4 explosive at stand-off distances from 8 m to 16 m. These targets formed part of two studies presented here: one, to observe the loading of the same geometry of target to an increasing shock intensity; and the second, to observe the response of one target to multiple blast impacts. Experimental data provides detailed data for sandwich panel response, which are often used in civil and military structures, where air-blast loading represents a serious threat. High-speed photography, with digital image correlation (DIC), and laser gauge systems were employed to monitor the deformation of these structures during the blasts. The experimental data provides for the development of analytical and computational models. Initial analysis of the blast experiments are presented alongside a finite element model to establish trends in deformation behaviour. Details of failure mechanisms and the conditions for the onset of failure are also discussed.